Barriers and Facilitators of Patient Engagement Activities to Improve Patient Safety in Healthcare Organizations: A Delphi-Based Expert Survey - Koch A; Brust L; Weigl M (Risk Management and Healthcare Policy)
Amelie Koch, Larissa Brust, Matthias Weigl Institute for Patient Safety (IfPS), University Hospital Bonn, Bonn, GermanyCorrespondence: Larissa Brust, Institute for Patient Safety (IfPS), University Hospital Bonn, Venusberg-Campus 1, Bonn, 53127, Germany, Email larissa.brust@ukbonn.dePurpose: In order to obtain sustainable healthcare, engagement of patients in patient safety improvement is vital. Drawing upon a multi-perspective approach, this study aimed to investigate perspectives of patients and healthcare professionals on key implementation factors (ie, barriers and facilitators) for effective patient engagement (PE) in healthcare organizations to improve patient safety.Patients and Methods: A two-round Delphi technique comprising semi-structured interviews and an online survey was applied to consolidate the individual perspectives of stakeholders and establish consensus on factors (expected, potential or experienced) that facilitate or mitigate successful implementation of PE in healthcare organizations (ie, all types, including hospital and outpatient medical practices). Adult, German-speaking experts in patient safety or PE (ie, with professional background or personal experience) were eligible to participate. Purposive and convenience sampling for inclusion of different healthcare professionals and patient representatives was established. Thirty-four panelists participated in data collection.Results: We identified eight key barriers and seven facilitators for effective patient engagement in healthcare organizations. Time constraints and perceived low effectiveness of patient engagement activities were deemed as most critical barriers. Supportive organizational culture, education and training opportunities, and clearly nominated responsibilities for patient feedback and engagement were rated as the most important facilitators. There were no statistically significant differences in the ratings between patient representatives and healthcare professionals.Conclusion: Our findings contribute to a deeper understanding of real-world implementation factors for effective patient engagement in healthcare organizations in Germany to improve patient safety. Our insights may further inform recommendations for future development and implementation of effective patient involvement in healthcare organizations, especially for similar countries with low levels of PE.Trial Registration: German Clinical Trials Register (ID: DRKS00031837).Keywords: patient involvement, patient participation, patient safety culture, healthcare, Delphi technique